UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW BERBANTUAN GEOGEBRA DI SMP TRISAKTI 2 MEDAN - Candi Krisna Martua Siahaan; Erlinawaty Simanjuntak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ mathematical problem-solving ability through the implementation of the Jigsaw cooperative learning model assisted by the GeoGebra application on the topic of solid geometry in grade IX at Trisakti 2 Medan Catholic Private Junior High School. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, acting, observing, and reflecting. The subjects were 22 students of class IX A and a mathematics teacher as a collaborator. Data were collected using teacher and student activity observation sheets and mathematical problem-solving tests, analyzed descriptively using both quantitative and qualitative approaches. The results revealed an improvement in both teacher and student activities as well as students’ mathematical problem-solving skills. Teacher activity increased from good to very good, while student activity improved from fair to good. Students’ mathematical problem-solving ability also progressed, with the final results in Cycle II showing 82% for understanding the problem, 78% for planning, 80% for calculating, and 76% for checking the results. These findings indicate that the Jigsaw model assisted by GeoGebra helps students visualize and comprehend mathematical concepts more effectively and systematically. Thus, the implementation of the Jigsaw cooperative learning model assisted by GeoGebra is effective in improving students’ mathematical problem-solving ability while fostering activeness, responsibility, collaboration, and critical thinking in mathematics learning.